Makna Kontekstual Ayat-ayat Pendidikan dalam Al-Qur'an Perspektif Linguistik Arab - Maesaroh, Maesaroh; Hidayat, Ade; Nasehudin, Nasehudin (Study Program of Arabic Language Teaching, 2026)
This study examines the contextual meaning of educational verses in the Qur'an through a comprehensive Arabic linguistic approach. Employing a qualitative library research method, this study analyzes 247 educational verses distributed across 52 surahs of the Qur'an from morphological, syntactic, semantic, and pragmatic perspectives. Data collection techniques involved documentation by identifying educational verses using Mu'jam al-Mufahras li Alfazh al-Qur'an, then inventorying key terms such as 'allama (to teach), tarbiyah (to educate), tafakkara (to think), and 'aqala (to reason), along with their derivations. Data analysis employed Arabic linguistic content analysis through four stages: (1) morphological analysis (al-tahlil al-sharfi) to identify derivation patterns and lexical meanings; (2) syntactic analysis (al-tahlil al-nahwi) to examine sentence structures and grammatical functions; (3) semantic analysis to reveal semantic fields and contextual meaning relations; and (4) pragmatic analysis to understand speech acts and communicative implicatures. The research findings indicate that the morphological structure of educational terms employs the fa''ala derivation pattern, indicating intensive, continuous, and holistic educational processes. Syntactic analysis reveals the dominance of jumlah fi'liyah patterns and imperative structures that create active learning dynamics. Semantic analysis identifies educational semantic fields encompassing cognitive dimensions ('ilm), wisdom (hikmah), critical thinking (tafakkur), and character building (adab). Pragmatic analysis reveals 127 directive speech acts, 68 assertive speech acts, and 52 expressive speech acts that consider situational contexts. The resulting contextual meanings are relevant to contemporary education in the areas of critical literacy, holistic learning, the development of higher-order thinking skills, and science-religion integration. This research provides methodological contributions to the development of Qur'anic exegesis through systematic, objective linguistic approaches.